Influence of Dextran Molecular Weight on the Physical Properties of Magnetic Nanoparticles for Hyperthermia and MRI Applications - Strbak, Oliver; Antal, Iryna; Khmara, Iryna; Koneracka, Martina; Kubovcikova, Martina; Zavisova, Vlasta; Molcan, Matus; Jurikova, Alena; Hnilicova, Petra; Gombos, Jan; Kadasova, Nina; Dobrota, Dusan (Nanomaterials (Basel, Switzerland), 2020)
Dextran-coated magnetic nanoparticles are promising biocompatible agents in various biomedical applications, including hyperthermia and magnetic resonance imaging (MRI). However, the influence of dextran molecular weight on the physical properties of dextran-coated magnetic nanoparticles has not been described sufficiently. We synthesise magnetite nanoparticles with a dextran coating using a co-precipitation method and study their physical properties as a function of dextran molecular weight. Several different methods are used to determine the size distribution of the particles, including microscopy, dynamic light scattering, differential centrifugal sedimentation and magnetic measurements. The size of the dextran-coated particles increases with increasing dextran molecular weight. We find that the molecular weight of dextran has a significant effect on the particle size, efficiency, magnetic properties and specific absorption rate. Magnetic hyperthermia measurements show that heating is faster for dextran-coated particles with higher molecular weight. The different molecular weights of the coating also significantly affected its MRI relaxation properties, especially the transversal relaxivity r2. Linear regression analysis reveals a statistically significant dependence of r2 on the differential centrifugal sedimentation diameter. This allows the targeted preparation of dextran-coated magnetic nanoparticles with the desired MRI properties. These results will aid the development of functionalised magnetic nanoparticles for hyperthermia and MRI applications.
Keywords: relaxivity; dextran; magnetic hyperthermia; diameter; MRI; magnetic fluid; physical properties; magnetic nanoparticles